ANALISIS KINERJA KEUANGAN KOPERASI WANITA PESONA MARTA (KOPWAPETA) KOTA PEKANBARU - Rizky Suhendy; Gimin '; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: This research aim to know and analyse monetary perfomance of Co-Operation Woman Pesona Marta(KOPWAPETA) Pekanbaru City if seen from his monetary ratio of year 2010,2011,2012,2013 and 2014. This research place is executed in Co-Operation environment Woman Pesona Marta (KOPWAPETA) Pekanbaru City. This Research is started from February up to November month 2016. As for research type quantitatif and qualytatif descriptitive research that is explaining result of research which in the form of coresponding financial statement file to monetary performance of co-operation. Source of data of this research is obtained file of responbility reporting official member of Co-Operation Woman Pesona Marta (KOPWAPETA) Pekanbaru City of year 2010 until year 2014. As for used file collecting technique that is with study method of documentation. Result of research indicate that monetary performance of Co-Operation Woman Pesona Marta (KOPWAPETA) of year 2010 until year 2014 have goodness. This matter because of condition of Ratio Likuditas, Solvency Ratio and Ratio Profitability which consist of Net Profit Margin (NPM) and of Return On Investment (ROI) continue to experience of the make-up of from year of to year.Keywords : Monetary Performance, Ratio of Likuiditas, Solvency Ratio, and RatioProtability.